2021
DOI: 10.5089/9781513572673.001
|View full text |Cite
|
Sign up to set email alerts
|

Sizing Up the Effects of Technological Decoupling

Abstract: This paper proposes channels through which technological decoupling can affect global growth, and embeds these different layers in a global dynamic macroeconomic model. Multiple scenarios are considered that differ along two dimensions: (i) the coalition of countries (hubs) that initiate the decoupling, and (ii) whether non-hub countries are also forced to decouple via 'preferential attachment' -i.e. by aligning themselves with the hub they trade most with. All global technology hubs lose across scenarios, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 3 publications
0
18
0
3
Order By: Relevance
“…stored at sea. Beginning mid-March, the trend reversed for less commoditized goods (those transported in containers and finished vehicles) started to dip dramatically (Figure 3), a consequence of companies halting production and households postponing purchases of durable goods (Peiris et al, 2021). Despite the gradual recovery during the ensuing period, the value of imports of the three largest developed economies was still about 25% below pre-crisis peaks by August 2010.…”
Section: Covid-19 Impact On Global Trade Flowsmentioning
confidence: 99%
“…stored at sea. Beginning mid-March, the trend reversed for less commoditized goods (those transported in containers and finished vehicles) started to dip dramatically (Figure 3), a consequence of companies halting production and households postponing purchases of durable goods (Peiris et al, 2021). Despite the gradual recovery during the ensuing period, the value of imports of the three largest developed economies was still about 25% below pre-crisis peaks by August 2010.…”
Section: Covid-19 Impact On Global Trade Flowsmentioning
confidence: 99%
“…Varadarajan et al (2020) concluded that US companies have significantly more to lose in the short term –in terms of both revenue and access to critical components and materials – because of their strong push to source and sell in China over the years. Using a global dynamic macroeconomic model, Cerdeiro et al (2021) focused on technological decoupling and found that all global technology hubs lose across various scenarios. Hu et al (2021) focused on trade decoupling and found that, during the scenario of complete decoupling, China's GDP will lose 3.65 per cent and the US only 1.04 per cent; the decoupling of technology‐intensive trade between the US and China will affect 2.1 per cent of China's GDP, but only 0.43 per cent of the US economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most previous research has been descriptive or qualitative. But some authors, including Hu et al (2021), Cerdeiro et al (2021), and Eppinger et al (2021), have built econometric models to predict the probable economic consequences based on scenario analysis (more analyses are noted in section 2).…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest a loss of about 1.2 percent of world GDP, which increases to 1.5 percent when barriers to trade are extended to other sectors as well. Cerdeiro et al (2021) employ a set of structural models to examine the costs of three different layers of fragmentation (trade, sectoral misallocation, and foreign knowledge diffusion), across a range of fragmentation scenarios. Their estimated welfare costs range from zero (as some countries gain from trade diversion) to 8.5 percent when accounting for all three layers of fragmentation.…”
Section: Introductionmentioning
confidence: 99%